Innovation in the Development of Synthetic and Natural Ocular Drug Delivery Systems for Eye Diseases Treatment: Focusing on Drug-Loaded Ocular Inserts, Contacts, and Intraocular Lenses - Letizia Pelusi; Domitilla Mandatori; Leonardo Mastropasqua; Luca Agnifili; Marcello Allegretti; Mario Nubile; Assunta Pandolfi (MDPI AG, 2023)
Nowadays, ocular drug delivery still remains a challenge, since the conventional dosage forms used for anterior and posterior ocular disease treatments, such as topical, systemic, and intraocular administration methods, present important limitations mainly related to the anatomical complexity of the eye. In particular, the blood-ocular barrier along with the corneal barrier, ocular surface, and lacrimal fluid secretion reduce the availability of the administered active compounds and their efficacy. These limitations have increased the need to develop safe and effective ocular delivery systems able to sustain the drug release in the interested ocular segment over time. In the last few years, thanks to the innovations in the materials and technologies employed, different ocular drug delivery systems have been developed. Therefore, this review aims to summarize the synthetic and natural drug-loaded ocular inserts, contacts, and intraocular lenses that have been recently developed, emphasizing the characteristics that make them promising for future ocular clinical applications.